Evaluation of the physicochemical properties of pectin extracted from Musa paradisiaca banana peels at different pH conditions in the formation of nanoparticles - David Arias; Johny Rodríguez; Betty López; Paula Méndez (Heliyon, 2021)
Colombia is one of the major producers and exporters of banana Musa paradisiaca. Its consumption is high then its agro-industrial wastes are important source to extract pectin. In the present study, inorganic acids (nitric acid and hydrochloride acid) and organic acids (citric acid and acetic acid) were evaluated to extract pectin from banana peels at pH 2 and 3, through acid hydrolysis during 1h at the temperature of 85 °C. The extraction yield, degree of esterification (DE) and intrinsic viscosity of the pectin were characterized. Nitric acid (NA) allowed to obtain higher extraction yield (54 ± 10%) and citric acid (CA) allowed to obtain higher DE (76.7 ± 2%). Additionally, the effect of polymer concentration and degree esterification, low degree of esterification (LDE, 33.1%) and high degree of esterification (HDE, 76.7%) were evaluated in the pectin nanoparticles formation. The pectin with HDE formed stable nanoparticles with a particle size of 255 ± 11 nm and the zeta potential value of -45 ± 3 mV, independently of the polymer concentration. Morphology analysis showed aggregated of the pectin nanoparticles.